6u+10=16

Simple and best practice solution for 6u+10=16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6u+10=16 equation:



6u+10=16
We move all terms to the left:
6u+10-(16)=0
We add all the numbers together, and all the variables
6u-6=0
We move all terms containing u to the left, all other terms to the right
6u=6
u=6/6
u=1

See similar equations:

| 4(x+10)=5x+3 | | 3(2s+6)=-19-5s | | −5(−2x−4)+5x−4=−29 | | 9-4+10x=7x+4+3x | | 4w+17=39 | | 7x-14=7(-2) | | 22/n=4 | | 8x(3x-1)=0 | | 2/8a-3=1/3a+6 | | -4+5p-10=4+8p | | 4j+4j-6j=20 | | 42-(3c+4)=2(c+4) | | -5h+11+2h=3(2-h)+5 | | -17=-5=3e | | 7x−2=12 | | 3m-2m+3m+2m-3m=9 | | 10q-q+3q+q-12q=8 | | y-2=3y-16 | | y^2-14y-240=0 | | 5x-11=2x-8 | | y^2-14-240=0 | | -10r+-10r-13r-4r=-11 | | 2x+3x+4x=81-4x | | k/(-7/2)=23/5* | | 10x3x-1=7+3+2 | | 8t-4+9=t7t+2 | | (8)^2x+3=64^3x | | 2(x-1)+8=4x | | 52x−4=42x−32 | | 12a−12a+3a−a=6 | | (16x=13)=(16x-7) | | 18r+5r-16r-4r=9 |

Equations solver categories